Crowdsourcing and Its Application - Mitrović, Jelena (Infotheca - Journal for Digital Humanities; Vol 14 No 1 (2013): Infotheca - Journal of Informatics and Librarianship, 2024)
The goal of this paper is to point out the importance of crowdsourcing and to present some of the most successful projects that are functioning on the basis of this management model that originated in the business world, but it found its way into the world of culture and science. The ways in which crowdsourcing systems function are explored, as well as the technologies they are most commonly based upon. Some necessary requirements for the success of crowdsourcing systems are determined and best practice examples described, with extra attention given to the Natural Language Processing (NLP) projects that are carried out via crowdsourcing.